(untitled) (Fiep Bulletin - online, 2013)
This study aimed to compare the performance of visually impaired athlete has to do with her or not relevant guide for the development of their motor skills. The research is characterized quantitative, aiming descriptive as technical procedure using survey data, being the type of field research. A sample of 12 male athletes sex (n = 12) divided into two groups (group A and group B). Group A consisted of 6 athletes visually impaired practitioners Athletics. The group B consisted of 6 athletes seers regarded guides. For that evaluated the following skills: agility (shutle run), with the test of 50m and kinesthetic perception (perception of distance jump), horizontal jump. For comparison of results obtained in both groups, we used the statistic t or t test. Unlike the visually impaired group and their guides are not significant, since the p-value obtained in the test run (0.4020) and in the jumping test (0.8739), taking into account the level of significance ? = 0.05. How ot obtained from both tests were below the level of significance, hypotheses and H0a H0B were accepted and H1b and H1b were refuted. The hypothesis states that H0a athletic performance compared to guide disabled athlete are equal with respect to race 50 meters, already H0B states that an athlete’s performance compared to guide disabled athlete are equal with respect to horizontal impulse.